Diagnosis of Chikungunya Virus in Febrile Patients From a Malaria Holoendemic Area. (August 2021) - Lobaloba Ingoba, Line; Adedoja, Ayodele; Peko, Simon Marie; Vairo, Francesco; Haider, Najmul; Kock, Richard; Ippolito, Giuseppe; Zumla, Ali; Nguimbi, Etienne; Pallerla, Srinivas Reddy; Velavan, Thirumalaisamy P; Ntoumi, Francine
HIGHLIGHTS: A report of a Chikungunya (CHIK) outbreak in the Republic of Congo in 2019 Malaria endemicity in Congo was also reported There was a 14% co-infection of CHIK and malaria IL-13 levels increased in patients with co-infection Molecular tools provided better diagnosis of CHIK infection Abstract: Introduction: Accurate diagnosis of chikungunya (CHIK) is essential for effective disease management and surveillance. In a cohort of febrile Congolese patients, available diagnostic methods widely used in CHIK diagnosis were evaluated. In addition, plasma cytokines were quantified in CHIK patients and those coinfected with malaria compared with healthy controls. Methods: Between June and November 2019, a total of 107 febrile patients with suspected CHIK were subjected to differential diagnosis both for CHIK and malaria. Patients were screened for CHIK virus using molecular diagnosis by real-time PCR, serologic testing by IgM-specific and IgG-specific ELISAs, and lateral flow-based method with rapid diagnostic test (RDT), while malaria diagnosis was confirmed by PCR methods. Pro-inflammatory (IL-12, IL-16, IFN-γ, TNF-α) and anti-inflammatory (IL-4, IL-10, IL-13) cytokines were quantified in patients and healthy controls by ELISA assays. Results: Molecular diagnoses revealed that 57% (61/107) were positive for CHIK by RT-PCR, while serologic testing revealed 31% (33/107) and 9% (10/107) seropositivity for anti- IgM and IgG, respectively. None of the patients were CHIK RDT-positive. Also, 27% (29/107) were PCR-positive for malaria. Among the malaria-positive patients, 14% (15/107) were co-infected with CHIK and 13% (14/107) were monoinfection. Plasma IL-12 and TNF-α levels were increased in patients with malaria and IL-13 levels were increased in patients with co-infection (p<0.05). Conclusion: Co-infection of malaria and CHIK were common in febrile Congolese patients. Real-time PCR was a better tool for detecting actual occurrences of CHIK in a malaria holoendemic area.